Anterior chamber depth measurements using Scheimpflug imaging and optical coherence tomography: Repeatability, reproducibility, and agreement. Issue 1 (January 2015) - Wang, Qinmei; Ding, Xixia; Savini, Giacomo; Chen, Hao; Feng, Yifan; Pan, Chao; Hua, Yanjun; Huang, Jinhai
Abstract : Purpose : To determine the repeatability, reproducibility, and agreement of anterior chamber depth (ACD) measurements obtained with 3 Scheimpflug cameras and an anterior segment optical coherence tomography (AS‐OCT) device. Setting : Eye Hospital of Wenzhou Medical University, Zhejiang, China. Design : Observational cross‐sectional study. Methods : Two observers took 3 consecutive measurements in healthy right eyes using each device to assess intraoperator repeatability. The mean values obtained at different sessions by the first operator were used to determine the intersession reproducibility. Three consecutive measurements obtained by the first operator at the first session were averaged and used to assess agreement. Results : The ACD measurements obtained by 2 observers in 71 eyes were highly repeatable using the 4 devices, with a test–retest repeatability of 0.04 to 0.07 mm for intraoperator repeatability. The interoperator and intersession reproducibility of ACD measurements were high, and the test–retest repeatability ranges of interoperator and intersession reproducibility were 0.06 to 0.07 mm and 0.05 to 0.08 mm, respectively. The ACD measurements of the 4 systems were sorted from the thickest to the thinnest (Galilei G2 > Visante > Sirius > Pentacam). The differences in the measurements were statistically significant except between the ACD measurements obtained by the Sirius device and the Visante device. However, good agreement with narrow 95% limits of agreement was found between these devices. Conclusions : The 4 devices provided high intraoperator repeatability and interoperator and intersession reproducibility for ACD measurements. Good agreement in ACD measurements was found between the devices in healthy eyes. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.